Correction: High prevalence of p16 staining in malignant tumors. - Noémi De Wispelaere; Sebastian Dwertmann Rico; Marcus Bauer; Andreas M Luebke; Martina Kluth; Franziska Büscheck; Claudia Hube-Magg; Doris Höflmayer; Natalia Gorbokon; Sören Weidemann; Katharina Möller; Christoph Fraune; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262877.].